(untitled) (Medical Forum Monthly, 2020)
Objective: To assess the efficacy of ETV in hydrocephalus related to the posterior fossa tumors in children. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the department of Neurosurgery Nishtar Hospital Multan from January 2018 to March 2020. Materials and Methods: A total of 45 patients were included in this study. Among the Group 1 was divided into Group 1a including 10 patients who underwent endoscopic third ventriculostomy (ETV) and Group 1b including 7 patients who underwent ventriculo-peritoneal (VP) shunt insertion for relieving intracranial hypertension, depending upon personal preference of neurosurgeons attending those patients. CT scan was done on all of these 45 patients after posterior fossa surgery and it was done repeatedly afterwards depending upon clinical conditions. Results: Later on, 8 (80 %) patients of group 1a, 2 (28.6 %) patients of group 1b, 13 (86.7%) patients of group 2, and 12 (92.3%) patients of group 3 were shunt free, and the difference among these groups was statistically significant. Conclusion: As the nature of postoperative hydrocephalus is obstructive, ETV should be regarded as a possible treatment procedure in all cases.